Critical successful factors for infrastructure financing in South Africa: enhancing the role of the new development bank - Ncube, Thulani (Graduate School of Business (GSB), 2021)
The study investigated the critical success factors of funding infrastructure development in South Africa and how they can be used by the BRICS' New Development Bank (NDB) to develop strategies for funding infrastructure development in the country. The quantitative research methodology was used in the investigation. The study used IDC and DBSA employees as the population and simple random sampling was used to select 20 employees from the two Development Finance Institutions (DFIs). Data was collected through questionnaires sent to 20 employees and descriptive analysis, confirmatory factor analysis and ranking analysis were then utilised to analyse the collected data. The results indicate that (DFIs) are the preferred source of funds for infrastructure development in South Africa and the appropriate strategy is the Private-Public Partnerships (PPPs). Critical success factors to successful infrastructure development funding were found to include project attributes, financing attributes, government attributes, the borrower or implementing agency attributes, and political and economic attributes. Factors that were found to have the highest impact on infrastructure development funding include economic viability of the project, the risk profile of borrower or implementing agency, availability of funding, strong financial instruments, financial risk, political and economic stability, political support and the social and economic benefits of the project. The first recommendation for the study is that it is suitable for the NDB to fund infrastructure development in the country and secondly that the NDB should employ PPPs to fund infrastructure development in the country. Furthermore, the DFI should only fund economically viable projects, projects that are accepted by the community and projects for borrowers or implementing agencies with a low-risk profile. Finally, the NDB ought to lobby the government for support and creation of conducive political and legal environments to guarantee successful funding of the infrastructure projects.